Disease-modifying therapies for multiple sclerosis - De Angelis, Floriana; John, Nevin A; Brownlee, Wallace J (BMJ (Online), 2018)
What you need to know: Disease-modifying therapies (DMTs) early in the course of active relapsing multiple sclerosis can prevent relapses, new brain and spinal cord lesions, and worsening neurological disability; Some DMTs are associated with potentially serious adverse reactions, and careful monitoring is required, usually through a specialist multiple sclerosis clinic; Newer DMTs have better short term outcomes than older DMTs, but there are insufficient data about their long term effectiveness and harms. A 32 year old woman with multiple sclerosis presented to her general practitioner with a five day history of numbness and weakness in the right leg. She felt well in herself and did not describe any symptoms to suggest an intercurrent infection. She had been taking weekly intramuscular injections of interferon beta-1a for the previous 18 months and reported flu-like symptoms that could last for up to 24 hours after each dose. She asked if there was a need to change her treatment and what alternatives were available.